The Role of Indonesian Language in Education: Building Character in the Millennial Era" - Irfan, Irfan (La Ogi : English Language Journal, 2024)
This article explores the challenges and efforts involved in the development of the Indonesian language within educational environments, particularly as a tool for shaping the character of the millennial generation. Education, as an official institution under the state's auspices, plays a crucial role in equipping individuals with the necessary skills to communicate effectively. However, in the current educational landscape, the use of Indonesian has diminished in quality, leading to concerns about its effectiveness as a medium of communication and character formation. This article discusses the importance of overcoming the fear of making mistakes, improving confidence in language use, and ensuring the correct application of Indonesian in both formal and informal educational settings. The aim is to revitalize the use of Indonesian language in education, thereby reinforcing its role in the holistic development of students and the preservation of the national identity.